Depiction of Vyala images at the entrance of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The details of the garbhagriha (sanctum sanctorum) are seen here at the bottom of the entrance of the Vishnu Temple. Flanking the chandrashila (moonstone) at the garbhagriha entrance is a band that shows vyalas (composite mythical creatures) pouncing upon and biting elephants from behind and tearing them apart with their claws.